2021
DOI: 10.3389/fpsyg.2021.642641
|View full text |Cite
|
Sign up to set email alerts
|

Not Too Much and Not Too Little: Information Processing for a Good Purchase Decision

Abstract: When deciding on an online purchase, consumers often face a plethora of information. Yet, individuals consumers differ greatly in the amount of information they are willing and able to acquire and process before making purchasing decisions. Extensively processing all available information does not necessarily promote good decisions. Instead, the empirical evidence suggests that reviewing too much information or too many choice alternatives can impair decision quality. Using simulated contract conclusion scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Information overload has been shown to be an important factor that negatively affects consumer behavior. This is because information overload not only leads to negative emotions such as anxiety, stress and dissatisfaction (Hu and Krishen, 2019) but also prevents consumers from identifying the important information they need from the large amount of information, making it more difficult for consumers to make purchase decisions (Chen et al, 2009a;Vogrincic-Haselbacher et al, 2021). We therefore propose the following hypothesis: H2.…”
Section: Moderating Effects Of Different Dimensions Of Consumer Visit...mentioning
confidence: 99%
“…Information overload has been shown to be an important factor that negatively affects consumer behavior. This is because information overload not only leads to negative emotions such as anxiety, stress and dissatisfaction (Hu and Krishen, 2019) but also prevents consumers from identifying the important information they need from the large amount of information, making it more difficult for consumers to make purchase decisions (Chen et al, 2009a;Vogrincic-Haselbacher et al, 2021). We therefore propose the following hypothesis: H2.…”
Section: Moderating Effects Of Different Dimensions Of Consumer Visit...mentioning
confidence: 99%
“…Previous studies have found similar effects of product-related confusion and identified the negative consequences (i.e. choice impairment) due to overloaded product selections through consumers' affective and cognitive responses (Tung et al, 2019;Vogrincic-Haselbacher et al, 2021). Also, choice overload has been pointed out as one of the issues in the current digital technology-driven retail environment that can cause confusion in consumer choice (Dholakia et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…To mitigate these negative consequences, fashion practitioners may need to develop strategies to alleviate a store's overloaded product information. For instance, reducing the number of product variations to a moderate level can lead to consumers' positive attitudes toward the store and improve their shopping experiences (the quality of shopping), especially for the consumers who perceive decision difficulty (Broniarczyk, 2018; Vogrincic-Haselbacher et al , 2021). Another practical suggestion includes managing product assortment and displaying efficiently by eliminating slow-moving items and allotting more space for frequently selling merchandise.…”
Section: Discussionmentioning
confidence: 99%
“…Visual complexity can pose challenges for consumers in their decision-making process (Wedel and Pieters, 2015). It can compromise the quality of their decisions when faced with excessive and complex information (Vogrincic-Haselbacher et al, 2021). When overwhelmed with information, consumers tend to adopt simple decision-making strategies (Grether and Wilde, 1983) and prefer single endorser brands which are easy to process information.…”
Section: Number Of Brand Endorsersmentioning
confidence: 99%